Dyslipidemia in children with type 1 diabetes: A cassandran cause or a pollyannic perspective - Sanjay Kalra (Journal of the Pakistan Medical Association, 2026)
Diabetes is a multifaceted disease, with each individual exhibiting varying aspects of the syndrome at different times in their life. Diabetes has been classified, for ease of understanding, into various types, including type 1 and type 2 diabetes.1 Many researchers, however, appreciate diabetes as a continuum, rather than as distinct numbered phenotypes. The use of descriptive such as double diabetes, type 1.5 diabetes, type 3 and type 5 diabetes bears testimony to this.2 Children and adolescents living with type 1 diabetes have unique necessities and needs.3 Diabetes care professionals should be aware of the nuances and niceties of their management. At the same time, they should not forget that persons living with type 1 diabetes are equally prone to the comorbidities and complications that occur in type 2 diabetes.4 Continue...